Simulations of a Current-Source Shunt Active Power Filter with Carrier-Based PWM and Periodic Sampling modulation techniques - Exposto, Bruno Fernandes (2011)
Bruno Exposto, Helder Carneiro, J. G. Pinto, Carlos Couto, João L. Afonso, "Simulations of a current-source Shunt Active Power Filter with Carrier-Based PWM and Periodic Sampling Modulation Techniques" Proceedings of the 2011-14th European Conference on Power Electronics and Applications (EPE 2011), pp.1-8, 30 Aug. – 1 Sept., 2011.